RANCANG BANGUN PROTOTIPE SISTEM KENDALI IRON REMOVAL FILTER (IRF) PADA UNIT PENGOLAHAN AIR BERSIH BERBASIS PLC - Karyadi, Kukuh; Suseno, Jatmiko Endro (Gema Teknologi, 2019)
Kukuh Karyadi, Jatmiko Endro Suseno in this paper explain that Water is a necessity of life that is very important for mankind. The availability of clean water has been sought to be fulfilled in various ways. One of them is by making a clean water treatment plant that can process water that is not yet suitable for consumption to be more feasible and ready to be consumed for everyday life. The operation of water treatment plant is still manually operated such as in the Iron Removal Filter (IRF) control system so that the processing is not easy to operate. To facilitate the operation of a clean water treatment unit, a control system based on a Programmable Logic Controller (PLC) is created on the Iron Removal Filter (IRF) processing unit.Â Control system consisting of PLC, relay circuit, power supply and Human Machine Interface (HMI), works to control the clean water processing unit including controlling the process on the IRF automatically. Also made a prototype of a water treatment plant consisting of an aerator unit, an IRF unit, a storage tank, several pumps and several control valves to be controlled by the control system in operation. The control system uses PLC as a control center because PLC is a controller that is simple, easy to program and very reliable as already widely used in the industrial world. The PLC brand used is Omron because it is cheap, reliable and has software named CX-Programmer which is easy in programming. The control system uses laptop computer as an HMI in the operation. HMI uses VTScada software and is connected to a PLC using OPC CX-Server software. The control system that is made can control the clean water processing unit in the form of a prototype. Operation on HMI is so easy and has a very attractive appearance. So it is highly recommended to be used in the actual clean water treatment unit